2018
DOI: 10.1016/j.envint.2018.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial lineages putatively associated with the dissemination of antibiotic resistance genes in a full-scale urban wastewater treatment plant

Abstract: Urban wastewater treatment plants (UWTPs) are reservoirs of antibiotic resistance. Wastewater treatment changes the bacterial community and inevitably impacts the fate of antibiotic resistant bacteria and antibiotic resistance genes (ARGs). Some bacterial groups are major carriers of ARGs and hence, their elimination during wastewater treatment may contribute to increasing resistance removal efficiency. This study, conducted at a full-scale UWTP, evaluated variations in the bacterial community and ARGs loads a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 82 publications
8
51
0
1
Order By: Relevance
“…Overall, the results are in line with current knowledge of the taxonomic distribution of these ARGs. This technique suggests that Aeromonadaceae, Acinetobacter, and Bacteroidetes are reservoirs of ARGs in this wastewater, as also recently suggested for another wastewater sample in Portugal using different approaches [26].…”
Section: Main Body Of Textsupporting
confidence: 67%
“…Overall, the results are in line with current knowledge of the taxonomic distribution of these ARGs. This technique suggests that Aeromonadaceae, Acinetobacter, and Bacteroidetes are reservoirs of ARGs in this wastewater, as also recently suggested for another wastewater sample in Portugal using different approaches [26].…”
Section: Main Body Of Textsupporting
confidence: 67%
“…Lee et al () also reported up to 4 log reductions of ARGs for a similarly configurated WWTP. Studies on UV disinfection show that UV treatment alone removes ARGs around 0 log reduction (Lee et al, ; Narciso‐da‐Rocha et al, ). The removal of ARGs by UV alone demonstrate a positive relationship with the dose of the UV applied (Sharma, Johnson, Cizmas, McDonald, & Kim, ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the coagulation (coag–floc) process produce up to 3 log reductions depending on the coagulants used (Li, Sheng, Lu, Zeng, & Yu, ). Studies on UV disinfection showed that the removal efficiencies vary around 0 log reduction (Narciso‐da‐Rocha et al, ). Despite the growing attention, removal of ARGs in WWTPs and the effect of ARG type on its inactivation efficiency via different treatment processes have not been completely understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of antibiotics for CCA were as per CLSI guidelines for Enterobacteriaceae [60]. For CET, antibiotic concentrations of ofloxacin were again as per CLSI guidelines for Pseudomonas aeruginosa while for ciprofloxacin a more environmentally relevant cut-off concentration (1 µg/mL) for resistance, which also has been previously reported, was chosen instead [61,62]. Resistance was estimated based on the ratio of the number of colonies enumerated in the presence of an antibiotic to the enumeration in its absence, using the equation below:…”
Section: Bacterial Countmentioning
confidence: 99%